2021
DOI: 10.1101/2021.02.12.21251621
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sub-diagnostic effects of genetic variants associated with autism

Abstract: While over 100 genes are now significantly associated with autism spectrum disorders (ASD), the penetrance of the variants affecting these genes remains poorly understood. Here, we quantified the prevalence of rare loss-of-function (LoF) mutations affecting 156 genes robustly associated with ASD (SPARK genes) using genetic data from more than 10,000 individuals with ASD and 100,000 undiagnosed individuals. We then investigated the clinical, brain imaging and genetic profiles of individuals heterozygous for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 90 publications
1
7
0
Order By: Relevance
“…Neither of these observations are true for ICVF. Although both common and rare genetic variants are associated with autism, questions still remain if these two broad classes of variants lead to the same phenotype in the brain [23, 25] and are enriched in the same biological processes [73]. The differential overlap between rare-genetic variants and common genetic variants for autism with SA and ICVF respectively, suggests, partly different neurological effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither of these observations are true for ICVF. Although both common and rare genetic variants are associated with autism, questions still remain if these two broad classes of variants lead to the same phenotype in the brain [23, 25] and are enriched in the same biological processes [73]. The differential overlap between rare-genetic variants and common genetic variants for autism with SA and ICVF respectively, suggests, partly different neurological effects.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies have investigated the neural correlates of common genetic variants associated with autism, indexed by polygenic scores (PGS). These studies demonstrated that PGS for autism is associated with global and regional alterations in cortical volume, cortical thickness (CT), and surface area (SA) [18, 25]. Of which, the PGS for autism association with CT is modified by age [26].…”
Section: Introductionmentioning
confidence: 99%
“…To be eligible, participants need to be over 2 years of age and have a diagnosed rare genetic condition associated with autism and/or have a diagnosis of autism (see figure 2). Decisions regarding which conditions and genetic variants to include have been made on the basis of published literature (36) and discussions with experts in the field (TB, LG), with consideration given to the penetrance, prevalence, and association with autism. For participants with a diagnosis of autism only, and where existing genetic information is available, recruitment will prioritise individuals within multiplex families and individuals with genetic variants associated with autism (see figure 2).…”
Section: Methods and Analysismentioning
confidence: 99%
“…FOXP1 (forkhead box protein P1) [136][137][138][139]. SYNGAP1 (synaptic Ras GTPase-activating protein 1) [140,141]. GABRA5 (gamma-aminobutyric acid type A receptor subunit alpha5) [142,143].…”
Section: Genes and Geneticsmentioning
confidence: 99%